Bridge management system within the strategic roads as an element of smart city. (January 2019) - Świt, G; Adamczak, A; Krampikowska, A
Abstract: A permanent increase of population in large urban centres - both in Poland and in the whole world - causes environmental pollution, demographic changes and, most of all, the growth of the traffic volume. A way to deal with all problems of cities is the performance of the Smart City conception, which allows to build intelligent solutions improving transport, energy technology, tourism and many other fields that constitute the economy. The basis of the operation should be an efficient communication infrastructure, because the dynamics of the economic development is significantly dependent on the efficiency and the reliability of the communication system. It can be also stated that the development of the transport networks, including those on highly urbanised areas, is essential to ensure proper functioning of economic and social life. Correctly conducted monitoring and the diagnostics of the bridges should help the road administration with managing these objects and with extending the lifetime period, so it should allow to optimise the completion period and the scope of possible renovation, repair or enforcement, and in the case of discovering that there are damages that endanger the safety of the construction, it should ensure justified removal from service. The article presents an example of the use of acoustic emission method for the assessment of the condition of My Thuan cable-stayed bridge by the Tien Giang river. The application of AE technique enables monitoring and following the processes occurring in the total volume of the structure, regardless of stress and deformations, but depending on the integrity of the construction, and this is of key importance for the durability of use and safe work of the bridge. Thanks to this, it enables the performance of the Smart Cities concept in relation to the intelligent infrastructure and ensuring a proper level of safety.